1995
DOI: 10.1029/94gl03219
|View full text |Cite
|
Sign up to set email alerts
|

Generation mechanism of tsunamis from the 1883 Krakatau Eruption

Abstract: The 1883 eruption of Krakatau generated a destructive tsunami which claimed about 34,000 lives. We compute the generation and propagation of tsunamis from three models previously proposed. They are 1) large‐scale caldera collapse of the northern part of Krakatau Island; 2) emplacement of pyroclastic flow deposits; 3) submarine explosion. We numerically solve the non‐linear shallow water equations on actual bathymetry. All three models displace the same volume (11.5 km³) of water in different ways. We compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 6 publications
1
68
1
2
Order By: Relevance
“…The modeling of the tsunami sources of the volcanic eruption is extremely difficult task and three hypotheses: caldera collapse, submarine explosion and pyrolastic flow are actively considered for the Krakatau event (Francis, 1985). Recently Nomanbhoy and Satake (1995) concluded that the submarine explosion model as the source of the largest tsunami is favored. The global behavior of the tsunami waves during the 1883 Krakatau event should be determined by the integral characteristics (period, amplitude) on the waves going out the Sunda Strait only, not by the details of tsunami generation.…”
Section: Hydrodynamic Long Wave Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The modeling of the tsunami sources of the volcanic eruption is extremely difficult task and three hypotheses: caldera collapse, submarine explosion and pyrolastic flow are actively considered for the Krakatau event (Francis, 1985). Recently Nomanbhoy and Satake (1995) concluded that the submarine explosion model as the source of the largest tsunami is favored. The global behavior of the tsunami waves during the 1883 Krakatau event should be determined by the integral characteristics (period, amplitude) on the waves going out the Sunda Strait only, not by the details of tsunami generation.…”
Section: Hydrodynamic Long Wave Modelingmentioning
confidence: 99%
“…The large difference in the computed and observed periods needs to be explained. According to the calculations by Nomanbhoy and Satake (1995), the characteristics period of the first two tsunami waves near the Krakatau Island, in the Sunda Strait is about 1 h (but the wave form is far from simplest sine), and, therefore, this low-frequency spectral component should be in the tsunami spectrum on any distance from the source, including the Port Blair. The computed tide-gauge record has the wide spectrum, and this low-frequency component is weak.…”
Section: Hydrodynamic Long Wave Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The eruption began on 20 May 1883 and volcanic activity continued for a few months until the final cataclysmic explosive events on August 26 and 27. Tsunamis were generated by emplacement of pyroclastic flow deposits, caldera collapse of the northern part of Krakatau Island and a huge submarine explosion (Nomanbhoy and Satake, 1995). The main catastrophic tsunami occurred on 27 August 1883 and caused the death of more than 36,000 people, as 295 villages and towns were destroyed or damaged in Java and Sumatra along the Sunda Strait (Simkin and Fiske, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The eruptive processes, and the source and time propagation of the tsunamis have been widely debated on the basis of observations, analysis of nearfield (<20 km from Krakatau volcano) pyroclastic deposits, tide and pressure gauge records, and numerical modelling (Verbeek 1886;Stehn 1929;Williams 1941;Ewing and Press 1955;Latter 1981;Self and Rampino 1981;Yokoyama 1981Yokoyama , 1987Camus and Vincent 1983;Francis 1985;Self 1992;Nomanbhoy and Satake 1995;Carey et al 1996;Mandeville et al 1996a, b;Choi et al 2003;Pelinovsky et al 2005;Maeno and Imamura 2011). This paper does not attempt to re-analyse the 1883 eruption and question the source of the tsunamis.…”
Section: Introductionmentioning
confidence: 99%